six frames for absence the sky shows through: a cross-dialogue with urban sceneries, the ideologies which have produced them, and the effects they have on the bodies they come into contact with (Abridged) - Pellikka, Essi; Pell (Taideyliopiston Kuvataideakatemia, 2024)
This thesis is the written component alongside the artistic component of the work “six frames for absence the sky shows through,” that was a part of the MFA graduation exhibition in 2024 in The Fine Arts Academy of Helsinki. The artistic component consists of two parts: a video work shown as a part of a screening schedule in the screening room of the Mylly building, and a map of the sources used in the voiceover of the video work, printed in risograph as an edition of seventy, and brought to the public later after the exhibition, at the Under The Leaf Art Book Fair, taking place in Art School Maa in September 2024 as a part of Drifts festival. The work is based on a longer term engagement of reading literary works from different points of the past century, alongside following the process of a failed construction project that took place in my hometown Tornio, in Northern Finland. Although the specific nature of the construction project has been the original motivation for the direction of the research, the work moves in an associative plain of multiple references and sources beyond the literary, attempting to form a cross-dialogue with the urban sceneries, the ideologies which have produced them, and the effects they have on the bodies they come into contact with. As a written extension of the work, this thesis can be described to carry on with the same concerns. Its emphasis though, is in trying to create a more heterogenous referential landscape aside of the literary, by including for example public discourse and recent regional or national projects of many scales, which clearest connecting factors may be the requirement for progress. Instead of reproducing the artistic component outside of the compulsory requirements, it will instead focus more on adding to the work: giving context and articulating the background impetuses behind the making, and the process which didn’t stop to the KK24 exhibition. The same as the logic of the work itself, the format of this thesis interprets the concept of low theory as a methodology and as a way of doing; attaching theory, literature and other textual and non-textual materials to marginal, personal or collective events of everyday life, fluctuating between scales and planes. The concepts of societal quests for progress and growth are included through for example an interest towards the ideologies which have pre-dated them and are attached to them, their compulsive formations, the societal systems and the material shapes they produce. Instead of discussing these big, complex themes as such, the text works more as a stroll through a city which it habits in the manner of a hunter-gatherer: picking up anything interesting it may find. What is the end result in the basket, may be a sort of a portrayal of the visited area, or at least a part of it. Alongside these, the silent narrator of the thesis is the prevalent question of the body; the porous body, the body which is not absolutely and perpetually adaptable, the body which evolution is tied to a different pace than that of the speeding-up cultural evolution, the body which develops symptoms as a response to its surroundings, the body which gets a rash when presented a utopia, and the body which often is denied during the quest for progress.
Keywords: low theory; progress; late capitalism; Tornio; kuvataide; taide; arkkitehtuuri; videotaide; modernismi; fi=tila-aikataiteet|sv=tid- och rumkonst|en=Time and Space Arts|